Effect of technology differences on chemical and sensory properties of Dalmatinska peČenica (pgI) - Krvavica, Marina (Array, 2021)
In the registration process of the protected geographical indication (PGI) of Dalmatinska pečenica, a research was conducted to determine the impact of differences in technology on the final product's chemical composition and sensory properties. Therefore, in three facilities in three Dalmatian counties, 35 samples of Dalmatinska pečenica were produced and divided into 7 groups, which differed in the initial weight of raw materials, composition, and amount of salting/brining mixture and the length of individual technological phases. After the processing phase, the samples were taken from each group, and the proportion of fat, protein, ash, water and NaCl was determined. A professional panel of 11 members assessed the sensory profile of Dalmatinska pečenica by descriptive sensory analysis. Chemical analysis determined the following average basic chemical composition of Dalmatinska pečenica: 5.68 % fat, 41.60 % protein, 44.80 % water and 7.63 % ash, and an average of 6.17 % represented NaCl. Dalmatinska pečenica produced from heavier raw meat (initial weight ≥3.5 kg) contained more intramuscular fat and water (P <0.05) and less proteins (P <0.05). The lower the initial weight of the raw pečenica and the higher the salt/ brine consumption per kg of raw meat, the higher the NaCl content in the mature pečenica, with the length of the salting/brining phase not significantly increasing the NaCl content in the pečenica. The sensory analysis determined the sensory profile and typical sensory properties of Dalmatinska pečenica, including characteristic cylindrical shape and colour, firm and elastic consistency, compact structure, uniform red cross-section, slightly salty taste, softness and solubility when chewed as well as an aroma characteristic of dry-cured pork products with a slightly expressed smoke aroma.